Added value of exercise test findings beyond traditional risk factors for cardiovascular risk stratification. (1st October 2019) - Bonikowske, Amanda R.; Lopez-Jimenez, Francisco; Barillas-Lara, Maria Irene; Barout, Ahmad; Fortin-Gamero, Sonia; Sydo, Nora; Allison, Thomas G.
Abstract: Background: Functional aerobic capacity (FAC) determined by treadmill exercise testing (TMET) is associated with cardiovascular (CV) disease mortality independent of traditional CV risk factors and is a potentially underutilized tool. The purpose of this study was to determine added prognostic value of reduced FAC and other exercise test abnormalities beyond CV risk factors for predicting total and CV mortality. Methods: The TMET database was queried for Minnesota patients (≥30 years) without baseline CV disease from September 21, 1993, through December 20, 2010. Risk factors and exercise abnormalities including low FAC (<80% predicted), abnormal heart rate recovery (<13 bpm), and abnormal electrocardiogram (ST depression ≥1 mm regardless of baseline) were extracted. Mortality data were obtained through February 2016. Patients were divided into 9 groups by abnormality number (0, 1, or ≥2) and risk factors (0, 1, or ≥2). Cox regression was used to determine mortality risk according to exercise abnormalities/CV risk factors, adjusted for age and sex. Results: 19, 551 patients met inclusion criteria; 1271 (6.5%) died over 12.4 ± 5.0 years' follow-up (405 [32%] CV deaths). Exercise abnormalities significantly modified risk for every number of CV risk factors. Hazard ratios (95% CI) for total mortality (0 vs ≥2 abnormalities) were 2.4 (1.9–2.9; P < .001) for 0 CV risk factors; 2.7 (2.2–3.3; P < .001), 1 risk factor; and 6.1 (4.8–7.7; P < .001), ≥2 risk factors. Similar results were noted for CV disease mortality. Conclusions: Exercise test abnormalities strongly predict mortality beyond traditional CV risk factors. Our results indicate that TMET should be considered for CV risk assessment. Highlights: Exercise test abnormalities strongly predict cardiovascular mortality. The worst survival occurs with multiple exercise abnormalities and risk factors. Exercise testing yields important prognostic data useful for risk assessment.